Management of a base station of a mobile network using a photovoltaic system. (June 2016) - Issaadi, Wassila; Khireddine, Abdelkrim; Issaadi, Salim
Abstract: The correct power supply for telecommunications relay stations, especially in areas where there is no electricity, is a handicap for operators to expand their clientele. It is on this sensitive topic that is taken this article. The photovoltaic solar energy appears as the most attractive solution: 1. To answer the energetic requires of a telecommunications base station. 2. To satisfy the needs of isolated uses, as is the case on many areas in our country. In this work, we study the best approach to transfer all the useful power from the photovoltaic generator to a telecommunications relay station (BTS or BSC). Knowing that the current–voltage characteristic of the generator (which depends on the illumination and temperature conditions), there is an operating point where the flowed power is on its maximum, the optimization consist of being permanently fixed on this point by acting automatically on the load made by the generator. This load adaptation is effected using a static converter including losses should be as low as possible, which can besides ensure a shaping function of the output rate (continuous–continuous conversion with voltage modification). We chose to use maximum power point MPPT research technology, based on different MPPT algorithms, controlled by a pulse-width modulation (PWM) signal. Modeling on Matlab/Simulink of the system different parts is proposed.